A computational essential dynamics approach to investigate structural influences of ligand binding on Papain like protease from SARS-CoV-2. (August 2022) - Singh, Ekampreet; Jha, Rajat Kumar; Khan, Rameez Jabeer; Kumar, Ankit; Jain, Monika; Muthukumaran, Jayaraman; Singh, Amit Kumar
Abstract: Papain like protease (PLpro) is a cysteine protease from the coronaviridae family of viruses. Coronaviruses possess a positive sense, single-strand RNA, leading to the translation of two viral polypeptides containing viral structural, non-structural and accessory proteins. PLpro is responsible for the cleavage of nsp1–3 from the viral polypeptide. PLpro also possesses deubiquitinating and deISGlyating activity, which sequesters the virus from the host's immune system. This indispensable attribute of PLpro makes it a protein of interest as a drug target. The present study aims to analyze the structural influences of ligand binding on PLpro. First, PLpro was screened against the ZINC-in-trials library, from which four lead compounds were identified based on estimated binding affinity and interaction patterns. Next, based on molecular docking results, ZINC000000596945, ZINC000064033452 and VIR251 (control molecule) were subjected to molecular dynamics simulation. The study evaluated global and essential dynamics analyses utilising principal component analyses, dynamic cross-correlation matrix, free energy landscape and time-dependant essential dynamics to predict the structural changes observed in PLpro upon ligand binding in a simulated environment. The MM/PBSA-based binding free energy calculations of the two selected molecules, ZINC000000596945 (−41.23 ± 3.70 kcal/mol) and ZINC000064033452 (−25.10 ± 2.65 kcal/mol), displayed significant values which delineate them as potential inhibitors of PLpro from SARS-CoV-2. Graphical Abstract: ga1 Highlights: PLpro is a indispensable viral protease. The present study investigate structural influences of ligand binding on PLpro. We have identified two promising lead candidates against PLpro.